Utilization of Mulberry Leaf Decoction (Morus Alba L.) as a Traditional Treatment for Fluor Albus in Women of Childbearing Age - Solichatin Solichatin; Nyna Puspita Ningrum; Nina Hidayatunnikmah; Desta Ayu Cahya Rosyida (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Fluor albus, or pathological vaginal discharge, is a common reproductive health disorder experienced by women of childbearing age (WUS). The primary cause is often related to Candida albicans fungal infection. Azole-based pharmacological therapy is known to be effective, but has the potential to cause resistance and side effects. This community service activity aims to improve the knowledge and skills of WUS in the Keputran Village, Surabaya, regarding the use of mulberry leaf decoction (Morus alba L.) as an alternative herbal treatment for fluor albus. The activity included health education, demonstrations on how to make herbal concoctions, and evaluation of participants' knowledge through discussions and questions and answers. The results showed a 90% increase in community knowledge regarding the prevention and treatment of fluor albus, and 85% of participants expressed interest in implementing this herbal treatment. This activity demonstrates that community empowerment through an educational approach and hands-on practice can increase awareness and independence in maintaining women's reproductive health naturally and sustainably.